ISTILAH HUKUM ADAT PADA MASYARAKAT DAYAK KANAYATN AHE - Irianti, April; Patriantoro, Patriantoro; Syahran, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractCustomary law is a law that regulates human behavior in relation to one another, both as a whole and a habit that truly lives in indigenous peoples because it is adhered to and maintained by community members, as well as all regulations concerning sanctions for violations and what is stipulated in the decisions of the adat officials. Customary law in this research is divided into terms of customary law, terms of actors, terms of cultural objects and terms of sanctions.The problem in this study is how the form of lingual units in customary law, the meaning of the terms in customary law, the form of supplementary class VII Indonesian learning texts in the 2013 curriculum are based on the terms in customary law. The purpose of this study is the description of all the terms of customary law. The method used in this study is descriptive and forms of qualitative research. the approach in this study uses a semantic approach. Sources of data in this study are informants. The technique used in this study is interview technique while data collection tools are recording devices and stationery. Based on the results of data analysis found 52 data on customary law terms divided into the first two forms of lingual units in the form of words (1) customary law, there are 7 data, (2) actors have 5 data, (3) cultural objects there are 6 data, ( 4) sanctions have 10 data. While the unit form in the form of phrase (5) customary law there are 12 data, (6) cultural objects there are 10 data, (7) sanctions there are 2 data.Â Keywords: Terms, Customary Law, Regulatsions, Supplements.Â